Loss of YTHDC1 m6A reading function promotes invasiveness in urothelial carcinoma of the bladder - Xu, Jinyun; Koch, Jonas; Schmidt, Claudia; Nientiedt, Malin; Neuberger, Manuel; Erben, Philipp; Michel, Maurice Stephan; Rodríguez Paredes, Manuel; Lyko, Frank (Experimental & molecular medicine, 2025)
Bladder cancer poses significant clinical challenges due to its high metastatic potential and poor prognosis, especially when it progresses to muscle-invasive stages. Here, we show that the m6A reader YTHDC1 is downregulated in muscle-invasive bladder cancer and is negatively correlated with the expression of epithelial‒mesenchymal transition genes. The functional inhibition or depletion of YTHDC1 increased the migration and invasion of urothelial cells. Integrative analysis of multimodal sequencing datasets provided detailed insights into the molecular mechanisms mediating YTHDC1-dependent phenotypes and identified SMAD6 as a key transcript involved in the invasiveness of urothelial carcinoma of the bladder. Notably, SMAD6 mRNA colocalized less with YTHDC1 in tumoral tissues than in paratumoral tissues, indicating disrupted binding during cancer progression. Our findings establish YTHDC1-dependent m6A reading as a critical epitranscriptomic mechanism regulating bladder cancer invasiveness and provide a paradigm for the epitranscriptomic deregulation of cancer-associated networks.